Computer-Assisted Language Instruction in South Yemeni Context: A Study of Teachers’ Attitudes, ICT Uses and Challenges - Ahmed, Sabri Thabit Saleh; Qasem, Bushra T. A.; Pawar, Sunil V. (International Journal of Language Education, 2020)
This study aimed at exploring South Yemeni EFL tertiary teachers’ attitudes towards implementing ICTs in their English language teaching, their current uses of such ICTs in their teaching and difficulties they encounter when implementing ICTs in their teaching for the purpose of getting an overall picture of ICTs-assisted language instruction in South Yemeni context and what is required for implementing a better ICTs-assisted language instruction at the concerned universities. Data were collected through a questionnaire webbed to 81 EFL teachers (n=81) and then analyzed by SPSS. The questionnaire consists of five-Likert items and open questions. Findings revealed that EFL teachers of the concerned universities held positive attitudes towards using ICTs in their teaching of English and there were no significant differences in teachers’ attitudes that can be attributed to gender, academic level or computer competence. They perceived ICTs as an effective tool in facilitating language teaching and learning, motivating students to learn and developing all language skills. However, their actual uses of such technologies in their classroom teaching were not up to the level required. A significant difference in teachers’ actual uses of technology can be attributed to their computer competence as those teachers with a high computer competence were found using ICTs more than their low computer competence counterparts. The study concluded that South Yemeni teachers’ lack of implementing ICTs in their EFL classes can be attributed to many factors such as lack of ICT tools in their departments, unavailability of internet and lack of computer competence and training. The study concluded with some recommendations that may help in implementing ICTs better in EFL education at the concerned universities particularly and at Yemeni universities generally.